Peran Kahoot Sebagai Media Pembelajaran Interaktif Dalam Mata Pelajaran IPAS Masa Kini - Yulia Ruti Cahyanti; Dina Celline Megasari; Nela Rofisian Rofisian (CV. ITTC INDONESIA, 2023)
The development of science and technology increasingly encourages innovative efforts to utilize technological results in the learning process. Teachers must be able to utilize the facilities provided by the school. Teachers can at least use cheap and effective tools, although simple but important to achieve the expected educational goals. The strategy used in this research is an embedded research strategy with a qualitative approach. Game-Based learning is one of many ways to enable learning experiences and increase student participation in collaborating in teaching and learning activities. It is also hoped that using the Kahoot application can increase students' enthusiasm and motivation in learning Natural and Social Sciences (IPAS). The Kahoot application is an effective and fun medium. Kahoot is an alternative to various types of interactive learning media, and the Kahoot application is style-oriented, making the learning process fun. Learning where students participate actively in competition with other students regarding the lessons they have learned or studied. Using the Kahoot app makes it more effective.